Conducting Clinical Trials in Twin Populations: A Review of Design, Analysis, Recruitment and Ethical Issues for Twin-Only Trials. (25th December 2021) - Yelland, Lisa N.; Scurrah, Katrina J.; Ferreira, Paulo; Calais-Ferreira, Lucas; Rankin, Monica; Denton, Jane; Harvey, Merryl; Lee, Katherine J.; Kendal, Evie; Craig, Jeffrey M.
Abstract: Although twins often participate in medical research, few clinical trials are conducted entirely in twin populations. The purpose of this review is to demonstrate the substantial benefits and address the key challenges of conducting clinical trials in twin populations, or 'twin-only trials'. We consider the unique design, analysis, recruitment and ethical issues that arise in such trials. In particular, we describe the different approaches available for randomizing twin pairs, highlight the similarity or correlation that exists between outcomes of twins, and discuss the impact of this correlation on sample size calculations and statistical analysis methods for estimating treatment effects. We also consider the role of both monozygotic and dizygotic twins for studying variation in outcomes, the factors that may affect recruitment of twins, and the ethics of conducting trials entirely in twin populations. The advantages and disadvantages of conducting twin-only trials are also discussed. Finally, we recommend that twin-only trials should be considered more often.